Adoption of alternative migratory tactics: a view from the ultimate mechanism and threshold trait changes in a salmonid fish. Issue 2 (18th September 2017) - Sahashi, Genki; Morita, Kentaro
Abstract : Partial migration, in which a portion of the population migrates while the rest of the population remains as residents, is a common form of migration. Alternative migratory tactics (AMTs) of partial migration are often determined by polygenic threshold traits. However, the ultimate mechanisms that drive inter‐population variations in threshold traits are not well understood. We present a simple schematic model to explain how the threshold trait changes with fitness consequences under opposing natural and artificial selection forces. We conducted a field test to evaluate the effects of migration difficulty (as a natural selective force) and selective captive breeding (as an artificial selective force) on threshold traits of a partially migratory fish. Male masu salmon Oncorhynchus masou in the Shari River system have AMTs divided into three population categories of hatchery, wild/above the waterfall, and wild/below the waterfall (control). The wild/above the waterfall salmon live in a high‐migration‐cost situation, and the threshold trait changed in a direction that promoted residency. In hatchery salmon, which are produced by migrant‐selective captive breeding, the threshold trait changed in a direction that promoted migration. In contrast, Dolly Varden charr Salvelinus malma displayed only resident tactics, and the threshold trait did not differ between the populations above and below the waterfall, indicating that environment did not explain the variation in the threshold trait. Our results support the model and suggest that opposing natural and artificial selection forces drive variations in the threshold traits and migratory patterns in the studied species. Our conceptual framework for the ultimate mechanism may help to better understand adoption of AMTs and production of diverse intraspecific traits in migratory animals.